1938
DOI: 10.1098/rspa.1938.0112
|View full text |Cite
|
Sign up to set email alerts
|

The saturation and immersion expansions and the heat of wetting

Abstract: In previous papers of this series evidence was advanced that: (i) The expansion which unactivated wood charcoal undergoes when adsorbing gases or vapours is directly proportional to its surface (free) energy lowering (Parts II and III). (ii) The Gibbs adsorption equation, relating the adsorption, the surface energy decrement of the charcoal, and the pressure of the gas, is valid except when a change of surface phase is in progress (Parts II and III).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1957
1957
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 2 publications
2
14
0
Order By: Relevance
“…McBain and Ferguson (1927) were the first to report swelling of sandstone, limestone, and cement caused by increase of air humidity, although they did not conduct any measurements of strain. Throughout next several decades, studies of adsorption-induced deformation were focused on charcoal (Bangham & Fakhoury, 1928;Bangham & Razouk, 1938;Briggs & Sinha, 1934;Meehan, 1927), porous glasses (e.g., Amberg & McIntosh, 1952), and silica (e.g., Reichenauer & Scherer, 2000, 2001. The order of observed deformation in carbons and glasses was about 10 À3 , while measurements on high-porous silica aerogel showed huge strain of 30%.…”
Section: Introductionmentioning
confidence: 99%
“…McBain and Ferguson (1927) were the first to report swelling of sandstone, limestone, and cement caused by increase of air humidity, although they did not conduct any measurements of strain. Throughout next several decades, studies of adsorption-induced deformation were focused on charcoal (Bangham & Fakhoury, 1928;Bangham & Razouk, 1938;Briggs & Sinha, 1934;Meehan, 1927), porous glasses (e.g., Amberg & McIntosh, 1952), and silica (e.g., Reichenauer & Scherer, 2000, 2001. The order of observed deformation in carbons and glasses was about 10 À3 , while measurements on high-porous silica aerogel showed huge strain of 30%.…”
Section: Introductionmentioning
confidence: 99%
“…18 Sorption of water and water vapor can stress the physical structure of BC because of exothermic graphitic sheet swelling. 19 These mechanisms result in swelling and expansion of the physical biochar structure, which improves the opportunity for further physical weathering. 20 Furthermore, fresh exposures of new biochar surfaces and fissures could accelerate microbial mineralization, 21 abiotic reactions, 22 or surface sorption phenomena.…”
Section: ■ Introductionmentioning
confidence: 99%
“…5 Others have observed that once biochar is exposed to soils, soil particles can fill exposed cavities and fissures 16 ( Figure S4 of the Supporting Information). These sealing processes could be accelerated by exothermic water sorption onto BC surfaces 19 and accelerate desiccation drying. It is conceivable that the physical accumulation of colloidal, dissolved, and particulate material, including soluble inorganic salts and/or aluminosilicates, would rapidly infill fractures and pores 43 ( Figure S4 of the Supporting Information).…”
mentioning
confidence: 99%
“…where ρ is the shale density in 3 kg/m , R is a molar gas constant ( 8.314 J/(mol K) ⋅ ), T is the reservoir temperature in K , p is the reservoir pressure in MPa , E is the Young's modulus in GPa , V is the gas adsorption amount in 3 cm /g , and L P is the Langmuir pressure in MPa . Seidle [57,58] presented a model describing the effect of matrix shrinkage deformation on the reservoir porosity. Therefore, the relationship between the change of porosity φ and matrix strain ε Δ can be proposed as…”
Section: Permeability Dynamic Changes Under Matrix Shrinkage and Strementioning
confidence: 99%